Genetic divergence in chironji (Buchanania lanzan) under semi-arid ecosystem of western India - SINGH, SANJAY; SINGH, A K; APPARAO, V V; BHARGAVA, R (The Indian Journal of Agricultural Sciences, 2016)
The present study was undertaken to evaluate the performance of 30 genotypes of chironji (Buchanania lanzan spreng) at Experimental Farm of Central Horticultural Experiment Station (CIAH), Vejalpur, Panchmahals (Godhra), Gujarat under rainfed hot semi-arid ecosystem of western India during the years 2011-2013. The results of study revealed that the different genotypes of chironji exhibited considerable variation for vegetative, floral, yield and physicochemical characters. The vegetative growth in terms of plant height, rootstock girth, plant spread (East-West) and plant spread (North-South) varied between 5.96-1.63m, 23.99-53.38cm, 1.40-5.10 m and 1.50-5.38 m, respectively. Time of flowering and fruit set ranged between 1st week February- 3rd week February and 3rd week February- 2nd week March, respectively. Maximum panicle length (35.13 cm) was noted in CHESC 1, while number of fruits per panicle was recorded highest in CHESC 7. Peak period of ripening in all the genotypes was recorded in May. Fruit yield, fruit weight, pulp per cent, TSS, acidity, total sugar and vitamin C varied from 1.00 kg-11.00 kg/plant, 0.94g-1.34g, 43.52- 63.06%, 19.05-23.900brix,1.00-1.34%,13.01-15.51% and 42.24-64.09%, respectively. Stone weight, shell weight, kernel weight and protein content ranged between 0.38-0.68g, 0.27-0.55 g, 0.08-0.15g and 23.53-31.36%, respectively. Based on the horticultural traits studied, the genotypes, CHESC7, CHESC2, CHESC 4 and CHESC11 were found to be promising under rainfed hot semi-arid conditions of western India. The genotype CHESC 7 was released as variety named as Thar Priya.